2018
DOI: 10.2147/oaem.s166026
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of injuries and predictors of inhospital mortality in trauma patients in Saudi Arabia

Abstract: BackgroundThe aim of this study was to describe the pattern of traumatic injuries and determine the predictors of inhospital mortality in patients admitted to the emergency department.Patients and methodsThis is a retrospective cohort study of 3,786 patients with traumat injuries admitted to the emergency department of King Abdulaziz Medical City, Riyadh, Saudi Arabia, between January 2012 and December 2014. Data on patient characteristics, trauma characteristics and outcomes were extracted from medical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…Construction work is the main contributor to falls from height in these countries [5][6][7][8]. Similar to reports from Qatar, Iraq, Oman, and Saudi Arabia, falls is a signi cant cause of injuries in the United Arab Emirates (UAE) [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 63%
“…Construction work is the main contributor to falls from height in these countries [5][6][7][8]. Similar to reports from Qatar, Iraq, Oman, and Saudi Arabia, falls is a signi cant cause of injuries in the United Arab Emirates (UAE) [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 63%
“…In our study, this is supported by the fact that the majority of recorded accidents that led to admissions was falls (47.8%), while MVAs had a similarly high incidence but a slightly lower proportion (42.4%). This finding is in contrast with that of a study published prior to the pandemic by Abolfotouh et al .,[ 9 ] where it was found that the majority of traumas were caused by MVAs (52%). Nevertheless, our findings are also supported by a similar study conducted in China by Zhu et al .,[ 10 ] where it was found that there was an increase in the incidence of falls, surpassing that of MVAs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study was conducted in China during the COVID-19 worldwide pandemic to examine the characteristics of traumatic fractures in the elderly; it was found that the population was predominantly female, and the most common fractures occurred in the hip due to falling from a standing position. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…Spleen injuries, as reported in literature, represent the most common event among abdominal traumas. [ 1 2 3 4 5 6 7 ] Spleen trauma prognosis is strictly related to the severity of the splenic injury and the trauma in general. The treatment of blunt splenic injuries (BSI) has changed significantly during the last 30 years with the non-operative management (NOM) that has become a standard of care both in children and in adults.…”
Section: Introductionmentioning
confidence: 99%